Adversities and Challenges on Listening and Speaking Learning of the English Language Students - Anna Riana Suryanti Tambunan; Willem Saragih; Isli Iriani Indiah Pane; Tiarnita M. S Siregar (Journal of English Language Studies, 2018)
The study aims to investigate the adversities and challenges on students’ listening and speaking learning. Thirty college students were involved in this study by distributing a questionnaire consisting of ten questions relating to their adversity and challenges in listening and speaking learning. Findings from this study indicate that the students confront some adversities. Being afraid to make mistakes and lacking vocabulary when speaking and listening are the most suggested to be the adversities. Building self-confidence is the best strategy to develop listening and speaking skills.